Recruitment and Retention Challenges in a Technology‐Based Study with Older Adults Discharged from a Geriatric Rehabilitation Unit. Issue 4 (July 2015) - McCloskey, Rose; Jarrett, Pamela; Stewart, Connie; Keeping‐Burke, Lisa
Abstract : Purpose: : Technology has the potential to offer support to older adults after being discharged from geriatric rehabilitation. This article highlights recruitment and retention challenges in a study examining an interactive voice response telephone system designed to monitor and support older adults and their informal caregivers following discharge from a geriatric rehabilitation unit. Methods: : A prospective longitudinal study was planned to examine the feasibility of an interactive voice telephone system in facilitating the transition from rehabilitation to home for older adults and their family caregivers. Patient participants were required to make daily calls into the system. Using standardized instruments, data was to be collected at baseline and during home visits. Findings: : Older adults and their caregivers may not be willing to learn how to use new technology at the time of hospital discharge. Poor recruitment and retention rates prevented analysis of findings. Conclusions and Clinical Relevancy: : The importance of recruitment and retention in any study should never be underestimated. Target users of any intervention need to be included in both the design of the intervention and the study examining its benefit. Identifying the issues associated with introducing technology with a group of older rehabilitation patients should assist others who are interested in exploring the role of technology in facilitating hospital discharge.